Multisystemic Inflammatory Syndrome and Thrombotic Microangiopathy as Complications of COVID-19 in a Child: A Case Report - Oi, Samira Shizuko Parreão; Muniz, Monique Pereira Rêgo; Faria, Igor Murad; Filho, Natalino Salgado; Brito, Dyego José Araújo de; Lages, Joyce Santos; Lauande, Letícia Pádua; Oliveira, Thina Klicia Mendonça; Cunha, Kaile de Araújo; Neves, Precil Diego Miranda de Menezes; Silva, Gyl Eanes Barros (Frontiers in Pediatrics, 2021)
Clinical presentations of the novel coronavirus (SARS-CoV-2) infection are quite varied, ranging from asymptomatic conditions to potentially fatal disease. The kidney is one of the affected targets of coronavirus disease (COVID-19) complications, and renal dysfunction is a significant prognostic factor for mortality. This report describes a series of clinical complications in a previously healthy child who developed nephritic syndrome with a concomitant SARS-CoV-2 infection. These complications include acute kidney injury that progressed to chronicity, multisystemic inflammatory syndrome, Kawasaki-like syndrome, and thrombotic microangiopathy.